Reforming the ICE regulations: What chance now - Mark Hall; John Purcell; Duncan Adam (University of Warwick, Industrial Relations Research Unit, 2015)
Drawing on analysis of 2004 and 2011 WERS data and extensive case studies of employee consultation bodies, this paper highlights major problems with the regulatory design and enforcement of the Information and Consultation of Employees Regulations 2004 and advocates reforms to improve their effectiveness in promoting and embedding meaningful consultation arrangements. Crucially, under the current regulations, the support of 10 per cent of the workforce is necessary for employees to initiate the statutory procedures. But union engagement with the legislation has been limited, and only rarely have non-union employees self-organised to trigger their consultation rights. The regulations have therefore proved peripheral, leaving wide scope for management inaction or unilateralism, and for unenforceable and sub-standard consultation arrangements. Key amendments proposed include lowering or preferably abolishing the workforce support threshold for triggering the regulations, integrating unions into the legal framework and applying minimum standards to voluntary agreements. The May 2015 election result means that there is little or no prospect government support for such changes during the current parliament. While moves underway at EU level may lead to some regulatory reform in this area, its implications for the UK will depend on the outcome of the upcoming renegotiation of the UK's relationship with the EU and referendum on continued UK membership.
Keywords: 330; Mitbestimmung; Internationaler Betriebsrat; Europäisches Arbeitsrecht; Rechtsangleichung; Großbritannien